2006
DOI: 10.1182/blood-2005-08-3255
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of human subjects expands both specific and bystander memory T cells but antibody production remains vaccine specific

Abstract: Human subjects maintain long-term immunologic memory against infective organisms but the mechanism is unclear. CD4 ؉ T-helper memory (Th mem )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 35 publications
7
42
0
2
Order By: Relevance
“…Our earlier study showed that bystander activation of CD4 1 T cells occurs in human subjects during a booster injection of TT, and that the responsive cells were memory T cells specific for other antigens [16]. To probe the bystander power of specific immunity, we have again utilized the TT response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our earlier study showed that bystander activation of CD4 1 T cells occurs in human subjects during a booster injection of TT, and that the responsive cells were memory T cells specific for other antigens [16]. To probe the bystander power of specific immunity, we have again utilized the TT response.…”
Section: Discussionmentioning
confidence: 99%
“…Such responses could contribute to the antigen-independent maintenance of T cells at different stages, including memory T cells. Our next goal is to test the effects of bystander stimulation on survival and functionality of transferred memory cells generated in vivo [6] rather than on cells stimulated in vitro, mimicking more closely our observations in human subjects [16]. Whatever the stage of the responding T cells, a balance between maintenance of memory and a potentially pathological effect of cytokine-activated cells must be struck.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[41][42][43] However, homeostatic maintenance and homeostatic expansion into lymphopenic hosts of naive CD4…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it was reported that sensitized TCs require different DS regimens to reduce DSA levels, including varying the IVIG dose and the number of PP cycles Thielke et al, 2005;Ferrari-Lacraz et al, 2006;Glotz et al, 2004;Rogers et al, 2011). Subsequent studies have demonstrated that susceptibility to IVIG/PP DS depends on immunoregulatory mechanisms, such as polymorphisms in cytokine genes, the frequency of regulatory cells, and hormonal backgrounds (Figure 7) (Glotz et al, 2004;Rogers et al, 2011;Zachary et al, 2003;Bas et al, 1998;Di Genova et al, 2006, 2010Jiang & Lechler, 2003, Amu et al, 2007Anderson et al, 2000;Hill & Sarvetnick, 2002;Kalil et al, 1989;Stasi et al, 2008;Stastny P et al, 2006;Yoo et al, 1995). Furthermore, the efficacy of DS has been reported to be different for DSAs and third-party HLA antibodies.…”
Section: Intravenous Immunoglobulin (Ivig)mentioning
confidence: 99%